2013
DOI: 10.1111/2049-632x.12057
|View full text |Cite
|
Sign up to set email alerts
|

Host Organelle Hijackers: a similarmodus operandiforToxoplasma gondiiandChlamydia trachomatis: co-infection model as a tool to investigate pathogenesis

Abstract: The bacterium Chlamydia trachomatis and the protozoan parasite Toxoplasma gondii are the causative agents of chlamydiosis and toxoplasmosis in humans, respectively. Both micro-organisms are obligate intracellular pathogens and notorious for extensively modifying the cytoskeletal architecture and the endomembrane system of their host cells to establish productive infections. This review highlights the similar tactics developed by these two pathogens to manipulate their host cell despite their genetic unrelatedn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 116 publications
(164 reference statements)
1
15
0
Order By: Relevance
“…IFN-γ is the most important cytokine that eliminates intracellular T. gondii by upregulating three pathways: (i) the immunoregulatory enzyme indoleamine 2,3-dioxygenase (IDO) to deplete local cellular tryptophan; (ii) inducible nitric oxide synthase (iNOS) to limit cellular arginine; (iii) interferon inducible immunity related GTPases (IRGs) and guanylate binding proteins (GBPs) to destroy the parasitophorous vacuole membrane (PVM), which is used by T. gondii to acquire nutrients, hijack host organelles and protect the parasite from host immune systems [ 29 , 32 ]. Notably, our study revealed that IFN-γ (Ifng), two iNOS (Nos2 and Nos3), one IDO (Ido1), seven IRGs (Irgm1, Irgm2, Iigp1, 9930111J21Rik2, Tgtp1, Tgtp2 and Gm12250) and nine GBPs (Gbp2, Gbp2b, Gbp3, Gbp4, Gbp5, Gbp6, Gbp8, Gbp9 and Gbp10) were upregulated.…”
Section: Discussionmentioning
confidence: 99%
“…IFN-γ is the most important cytokine that eliminates intracellular T. gondii by upregulating three pathways: (i) the immunoregulatory enzyme indoleamine 2,3-dioxygenase (IDO) to deplete local cellular tryptophan; (ii) inducible nitric oxide synthase (iNOS) to limit cellular arginine; (iii) interferon inducible immunity related GTPases (IRGs) and guanylate binding proteins (GBPs) to destroy the parasitophorous vacuole membrane (PVM), which is used by T. gondii to acquire nutrients, hijack host organelles and protect the parasite from host immune systems [ 29 , 32 ]. Notably, our study revealed that IFN-γ (Ifng), two iNOS (Nos2 and Nos3), one IDO (Ido1), seven IRGs (Irgm1, Irgm2, Iigp1, 9930111J21Rik2, Tgtp1, Tgtp2 and Gm12250) and nine GBPs (Gbp2, Gbp2b, Gbp3, Gbp4, Gbp5, Gbp6, Gbp8, Gbp9 and Gbp10) were upregulated.…”
Section: Discussionmentioning
confidence: 99%
“…To facilitate access to key nutrients that would otherwise be difficult to obtain, vacuole-dwelling pathogens intersect host membrane trafficking pathways (Pizarro-cerdá, Charbit, Enninga, & Lafont, 2016) and/or recruit host organelles to the outer vacuole membrane for nutrient scavenging (Plattner & Soldati-Favre, 2008). Striking examples of host organelle recruitment have been documented in cells infected with Chlamydia spp or Toxoplasma gondii (for a review, see Romano & Coppens, 2013), both of which attract host endoplasmic reticulum, mitochondria (Matsumoto, Bessho, Uehira, & Suda, 1991), Golgi membranes, endo-lysosomes, and lipid droplets (Kumar, Cocchiaro, & Valdivia, 2006;Nolan, Romano, & Coppens, 2017) to their vacuoles.…”
Section: Introductionmentioning
confidence: 99%
“…Amastigotes did not consistently co-localise with the host Golgi apparatus (Figure 2a, Supplemental Figure 1a) or the microtubule organising centre (MTOC, arrowhead; Figure 2b, Supplemental Figure 1b). Cytosolic amastigotes were always found enveloped by the host endoplasmic reticulum (ER; Figure 2c, Supplemental Figure 1c) but without obvious enrichment of host ER around the intracellular T. cruzi amastigotes (Figure 2c) as seen with vacuolarpathogens that actively recruit host ER(Romano & Coppens, 2013).The ubiquitous nature of the ER makes it difficult to draw any conclusions regarding specificity of any interactions occurring between the parasites and this host organelle. Contrasting this pattern is the more limited, defined branching network of the host mitochondria, within which intracellular amastigotes were consistently found to be embedded(Figure 2d, Supplemental Figure 1d-f).…”
mentioning
confidence: 99%
“…One hallmark of a T. gondii infection is the ability of the parasite to alter host cell pathways by using the PV membrane as a signaling platform or by secreting bioactive factors into the host cytoplasm and nucleus (28,29). T. gondii is also notorious for interacting with many host cell structures and organelles that surround the PV (30). Despite the discovery of N. caninum 30 year ago, many aspects of its intracellular behavior, including host cell interaction and nutrient uptake, have not been thoroughly studied.…”
mentioning
confidence: 99%